ERRORS IN CONSECUTIVE INTERPRETING: A CASE OF JESSICA KUMALAWONGSO’S COURT - Putri Pridani Malau; Syahron Lubis; Umar Mono (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study aimed to analyze the main types of errors found in the consecutive interpreting (CI) in Jessica Kumalawongso’s trial court and to indicate its causes. The research method used is the descriptive qualitative method by means of the secondary data taken from Kompas TV, uploaded on YouTube in 2016 consisting of three videos of the justifications of Jessica's attorney, toxicologist and forensic pathologist before the interpreter in order to counter the public prosecutor in the courtroom. They were, then, classified into both the source and the target languages by analyzing their types of error leading to the finding of the main types and subtypes of errors. The result of this study is that based on Gonzales theory on the consecutive interpreting, 67 errors with six out of eight main types are found at the entire selected videos. The six main types of errors detected in the court proceedings are non-conservation of paralinguistic features, inadequate language proficiency, addition, omission, distortion and register conservation.